2012
DOI: 10.1111/j.1744-7917.2012.01541.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and behavioral analysis of the cuticular hydrocarbons from Asian citrus psyllid, Diaphorina citri

Abstract: Huanglongbing (HLB) is the most destructive disease of citrus worldwide. The Asian citrus psyllid, Diaphorina citri Kuwayama (Hemiptera: Psyllidae), is the vector of the phloem-inhabiting bacterium, Candidatus Liberibacter asiaticus, which is presumed to cause HLB in Florida citrus. Laboratory and field studies were conducted to examine the behavioral responses of male and female D. citri to their cuticular extracts. In olfactometer assays, more male D. citri were attracted to one, five, or 10 female cuticular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 50 publications
1
27
1
Order By: Relevance
“…These compounds were present in quantities that varied according to sex and age. While sex linked differences appear to be important for mate attraction in C. pyricola and D. citri (Guédot et al 2009b; Mann et al 2012, we found no similar evidence for A. dobsoni. We suggest that age related differences in the CHCs of A. dobsoni probably reflect losses through abrasion given that the molecular weights and boiling points of most of the CHCs are probably too high for them to volatilize to any significant extent.…”
Section: Discussioncontrasting
confidence: 94%
See 4 more Smart Citations
“…These compounds were present in quantities that varied according to sex and age. While sex linked differences appear to be important for mate attraction in C. pyricola and D. citri (Guédot et al 2009b; Mann et al 2012, we found no similar evidence for A. dobsoni. We suggest that age related differences in the CHCs of A. dobsoni probably reflect losses through abrasion given that the molecular weights and boiling points of most of the CHCs are probably too high for them to volatilize to any significant extent.…”
Section: Discussioncontrasting
confidence: 94%
“…Sex related differences in CHC profiles also have been reported in C. pyricola and D. citri (Guédot et al 2009b; Mann et al 2012 females produce higher quantities of 13 MeC compared to post diapause males (Guédot et al 2009b ), while D. citri females produce more C H O compared to conspecific males (Mann et al 2012 ). We also found that the CHC profiles of both sexes vary with age.…”
Section: Sex and Age Specificitysupporting
confidence: 84%
See 3 more Smart Citations